Parsing distfix operators - Peyton Jones, Simon (Communications of the ACM, 1986)
The advantages of user-defined distfix operators – a syntactic convenience that enhances the readability of programs – can be obtained as an extension of almost any programming language without requiring dynamic changes to the parser.